Increasing the security and traceability of biological samples in biobanks by blockchain technology. (April 2023) - Ortiz-Lizcano, María Isabel; Arias-Antunez, Enrique; Hernández Bravo, Ángel; Caminero, María Blanca; Rojo Guillen, Tomás; Nam Cha, Syong Hyun
Highligths: Introduction of biobank as a case study for the application of blockchain technology. Development of smart contract for increasing the security and traceability of biological samples in biobanks using blockchain. No other similar works have been found in the literature been biobanks one of the essential services for biological research. Abstract: Background and Objective: One of the main tasks in a biobank consists in storing biological samples in a high-quality condition in order to future research. At moment, there exist many applications to manage a biobank. However, in general, these are web-based applications. In these web-based applications different tasks can be done. Among them, it is possible to remark the following: informed consent, confidentiality, non-profit, respect for quality and safety standards, including traceability of samples. In this paper, we describe a blockchain smart contract to ensure the traceability of the processes done in a biobank meaning a step forward to guarantee this traceability. Methods: Use of blockchain technology to improve security, integrity and traceability of the processes carried out in a biobank. In particular IBM Hyperledger Fabric. Results: As a result, a set of smart contracts have been developed describing the biobank processes. Conclusions: Improvement of the security, integrity, and traceability of samples in biobanks.